A novel bi‐allelic loss‐of‐function mutation in STIM1 expands the phenotype of STIM1‐related diseases. Issue 1 (29th March 2021) - Salvi, Alexandra; Skrypnyk, Cristina; Da Silva, Nathalie; Urtizberea, Jon Andoni; Bakhiet, Moiz; Robert, Catherine; Lévy, Nicolas; Megarbané, André; Delague, Valérie; Bartoli, Marc
Abstract: STIM1, the stromal interaction molecule 1, is the key protein for maintaining calcium concentration in the endoplasmic reticulum by triggering the Store Operated Calcium Entry (SOCE). Bi‐allelic mutations in STIM1 gene are responsible for a loss‐of‐function in patients affected with a CRAC channelopathy syndrome in which severe combined immunodeficiency syndrome (SCID‐like), autoimmunity, ectodermal dysplasia and muscle hypotonia are combined. Here, we studied two siblings from a consanguineous Syrian family, presenting with muscle weakness, hyperlaxity, elastic skin, tooth abnormalities, dysmorphic facies, hypoplastic patellae and history of respiratory infections. Using exome sequencing, we have identified a new homozygous frameshift mutation in STIM1 : c.685delT [p.(Phe229Leufs*12)], leading to a complete loss of STIM1 protein. In this study, we describe an unusual phenotype linked to STIM1 mutations, combining clinical signs usually observed in different STIM1‐related diseases. In particular, we confirmed that the complete loss of STIM1 function is not always associated with severe immune disorders. Altogether, our results broaden the spectrum of phenotypes associated with mutations in STIM1 and opens new perspectives on the pathological mechanisms associated with a defect in the proteins constituting the SOCE complex. Abstract :